Air pollutions affect restaurant and foodservice industry in China - Tian, Xu; Min, Shi; Shen, Jiexi; Hong, Qianqian; Headey, Derek D.; Zhao, Fangxiao; Wang, Xiaobing (Oxford University Press, 2025)
This study examines the impact of air pollution on food away from home (FAFH) consumption in 52 cities across 20 provinces of China, focusing on expenditures for online food delivery (online FAFH) and dine-in restaurants (offline FAFH). Using unique daily aggregated city-level consumption data linked with hourly air quality data, we employ both semiparametric and parametric models to uncover a positive relationship between PM2.5 levels and online FAFH, contrasted by a significantly negative relationship with offline FAFH. Our analysis reveals that shifts in consumer demand for food services on polluted days, coupled with changes in urban mobility patterns, contribute to these outcomes. We also detect temporal variations based on meal type, enhancing our understanding of how air pollution influences food consumption behavior. The findings indicate that increased PM2.5 levels lead to a net loss in restaurant revenue, a reduction in greenhouse gas emissions, and an increase in plastic waste. These findings contribute to a deeper understanding of the multifaceted impacts of air pollution on FAFH and corresponding economy and environmental implications.